Children with cerebral visual impairment related visual issues in the classroom (Kairaranga, 2023)
Cerebral visual impairment is a high incidence visual issue with a prevalence rate of 3.4% of children in mainstream education (Williams et al., 2021). However, it is still a very unknown condition with very little awareness in the general public (Ravenscroft et al., 2021). The aim of this research was to better understand how CVI related visual issues impact children in the mainstream classroom. Ten parents and eleven classroom teachers of eleven children with CVI related visual issues participated in the research, which used interviews and focus groups to develop a better understanding of the children and to ascertain the effectiveness of a range of strategies that were implemented to support the children throughout the research period. This was shorter than planned due to the COVID pandemic and school lockdowns. The research found that 82% of the children had learning support needs, 100% had emotional support needs, and 91% experienced challenges with social interactions. The CVI education sessions, decluttering, mindfulness, gratitude and calm breaks all helped the children, however the research period was not long enough to assess the overall effectiveness of the strategies and further research is needed in this area.